Hypokalemia as a sensitive biomarker of disease severity and the requirement for invasive mechanical ventilation requirement in COVID-19 pneumonia: A case series of 306 Mediterranean patients. (November 2020) - Moreno-Pérez, Oscar; Leon-Ramirez, Jose-Manuel; Fuertes-Kenneally, Laura; Perdiguero, Miguel; Andres, Mariano; Garcia-Navarro, Mar; Ruiz-Torregrosa, Paloma; Boix, Vicente; Gil, Joan; Merino, Esperanza; ,; Asensio, Santos; et al.
Highlights: There is a high prevalence of hypokalemia among patients with COVID-19 pneumonia. This suggests the presence of a disorder in renin–angiotensin system activity. Hypokalemia is associated with the requirement for invasive mechanical ventilation. Hypokalemia appears to be a sensitive biomarker for the progression of severity in COVID-19. Serum levels of potassium should be monitored closely in these patients. Abstract: Objectives: Serum levels of potassium (K + ) appear to be significantly lower in severe cases of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and the clinical significance of this is unknown. The objective was to investigate whether hypokalemia acts as a biomarker of severity in coronavirus disease 2019 (COVID-19) pneumonia and is associated with major clinical outcomes. Methods: A retrospective cohort study of inpatients with COVID-19 pneumonia (March 3 to May 2, 2020) was performed. Patients were categorized according to nadir levels of K + in the first 72 h of admission: hypokalemia (K + ≤3.5 mmol/l) and normokalemia (K + >3.5 mmol/l). The main outcomes were all-cause mortality and the need for invasive mechanical ventilation (IMV); these were analyzed by multiple logistic regression (odds ratio (OR), 95% confidence interval (CI)). Results: Three hundred and six patients were enrolled. Ninety-four patients (30.7%) had hypokalemia and these patients showed significantly higher comorbidity (Charlson comorbidity index ≥3, 30.0% vs 16.3%; p = 0.02) and CURB65 scores (median (interquartile range): 1.5 (0.0–3.0) vs 1.0 (0.0–2.0); p = 0.04), as well as higher levels of some inflammatory parameters at baseline. After adjustment for confounders, hypokalemia was independently associated with requiring IMV during the admission (OR 8.98, 95% CI 2.54–31.74). Mortality was 15.0% ( n = 46) and was not influenced by low K + . Hypokalemia was associated with longer hospital and ICU stays. Conclusions: Hypokalemia is prevalent in patients with COVID-19 pneumonia. Hypokalemia is an independent predictor of IMV requirement and seems to be a sensitive biomarker of severe progression of COVID-19.